2018
DOI: 10.3390/fermentation4030080
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall and Whole Cell Proteomes Define Flocculation and Fermentation Behavior of Yeast

Abstract: Flocculation is one of the most important characteristics of brewing yeast as it allows for the easy and cheap removal of cells after fermentation. The genes responsible for both the Flo1 and NewFlo flocculation phenotypes are well characterized. However, the relationship between Flo protein abundance and flocculation efficiency is poorly understood. In this present study, we used mass spectrometry proteomics to compare the cell wall and whole cell proteomes of commercial yeast strains with diverse flocculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…This means that this conserved aspartic acid motif is important and should not be mutated, consistent with the observation throughout the entire epithelial adhesin family (Maestre-Reyna et al, 2012). The residues N224, V226 and W228 have strong interactions with Ca 2+ which is located in the binding site (K. V. Goossens et al, 2015) and involved in the binding of carbohydrates (Kerr, McDiarmid, Fraser, & Schulz, 2018). Therefore, these residues will not be considered for mutation in order to avoid disrupting the oligomannose binding.…”
Section: Alanine Scanning Mutagenesissupporting
confidence: 57%
“…This means that this conserved aspartic acid motif is important and should not be mutated, consistent with the observation throughout the entire epithelial adhesin family (Maestre-Reyna et al, 2012). The residues N224, V226 and W228 have strong interactions with Ca 2+ which is located in the binding site (K. V. Goossens et al, 2015) and involved in the binding of carbohydrates (Kerr, McDiarmid, Fraser, & Schulz, 2018). Therefore, these residues will not be considered for mutation in order to avoid disrupting the oligomannose binding.…”
Section: Alanine Scanning Mutagenesissupporting
confidence: 57%
“…WLP775 is a standard yeast for dry ciders and may retain the flavors from apples [56]. Prior work demonstrated that cider produced using WLP775 exhibits higher flocculation behaviors than BY4743, but there is no research for WLP775 focused on its contribution to cider flavor [57]. In this research, WLP775 cider had a distinguished vegetal aroma, whereas Maurivin B-fermented ciders had higher levels of floral aromas detected.…”
Section: Sensory Analysismentioning
confidence: 77%
“…Whole Cell Sample Preparation -Proteins from yeast whole cell extracts were prepared for LC-MS/MS proteomics as previously described 48 . Briefly, harvested cells were resuspended in non-denaturing buffer with protease inhibitors, lysed by bead beating, cysteines were reduced/alkylated, and centrifuged.…”
Section: Sugar and Amino Acid Quantification By Multiple Reaction Mon...mentioning
confidence: 99%